2018
DOI: 10.1021/acs.jpclett.8b01586
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Sampling of the Cavity of the GroEL Nanomachine by Protein Substrates Probed by Paramagnetic Relaxation Enhancement

Abstract: The chaperonin GroEL is a 800 kDa nanomachine comprising two heptameric rings, each of which encloses a large cavity or folding chamber. The GroEL cycle involves ATP-dependent capping of the cavity by the cochaperone GroES to create a nanocage in which a single protein molecule can fold. We investigate how protein substrates sample the cavity prior to encapsulation by GroES using paramagnetic relaxation enhancement to detect transient, sparsely populated interactions between apo GroEL, paramagnetically labeled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
(62 reference statements)
1
9
0
Order By: Relevance
“…The separation between region 1 and the other two regions is sufficient to permit Aβ42 to contact two adjacent subunits of GroEL simultaneously. In addition, the methionine/glycine-rich C-terminal disordered tail of GroEL may also transiently contact bound Aβ42, as has been demonstrated using paramagnetic relaxation enhancement measurements for the interaction of a small folded SH3 domain with GroEL (31).…”
Section: Resultsmentioning
confidence: 87%
“…The separation between region 1 and the other two regions is sufficient to permit Aβ42 to contact two adjacent subunits of GroEL simultaneously. In addition, the methionine/glycine-rich C-terminal disordered tail of GroEL may also transiently contact bound Aβ42, as has been demonstrated using paramagnetic relaxation enhancement measurements for the interaction of a small folded SH3 domain with GroEL (31).…”
Section: Resultsmentioning
confidence: 87%
“…The data show at atomic resolution that the chaperones interact with the model clients Im7 and SH3 through their locally frustrated regions, regardless of the local structure or a specific sequence motif (Figure ). Intriguingly, the same recognition site on SH3 was also shown to be the binding site of the ATP‐dependent chaperone GroEL, and the same principle of recognizing frustration was also found to underlie dimer formation of the chaperone TF . Overall, these data indicate that the principle of recognizing frustrated segments in native clients might be a general functional feature of molecular chaperones.…”
Section: Chaperones Recognize Frustrated Surfaces Of Client Proteinsmentioning
confidence: 99%
“…Recent studies on the interactions between chaperones Spy, Skp and SurA and model clients Im7 and SH3 suggested a mode of interaction, in which chaperones recognize and bind locally frustrated surfaces of client proteins in a dynamic way . The same binding site on SH3 was also found to be engaged in interaction with the chaperonin GroEL, further supporting the notion that recognizing locally frustrated regions could be a common principle for chaperone‐client interactions where the client is a natively well‐folded protein . Moreover, a random mutagenesis study of GroEL‐client interaction using green fluorescent protein (GFP) as a model substrate demonstrated that mutations at highly frustrated positions correlate with decreased GroEL dependence during folding, whereas mutations at low frustration positions correlate with increased GroEL dependence .…”
Section: Chaperone‐client Interactionsmentioning
confidence: 70%